Uma cidade se faz de sonho: entre o real e o ideal: memórias e experiências na paisagem urbana de Uberlândia/MG (2000-2009) - Samora, Mariana Camin (2010)
This paper problematizes the social experiences lived by different workers in Uberlândia/MG considering some of the political intervention projects dedicated to reorganizing and making the city public areas more adequate, during the years of 2000 to 2009, more specifically, during the campaign Uberlândia without alms to prevent begging and the Project Olho Vivo - to prevent criminality. I analyse the lifestyle of a typical group of workers from Uberlândia beggars, flanelinhas , street salespeople, paper collectors and wagoners aiming to comprehend, not only how these subjects leave their traces on the city day by day, but mainly, how they reconstruct their values, meanings and expectations about surviving in Uberlândia. It s of vital value to investigate, via workers life stories, their way of seeing social relations without, however, losing sight of their daily struggle for the right to belong in the city, the tensions and resistances, the power relations, problematizing the ways their memories are elaborated throughout time. Amidst the scenario of conflicting relations, I prioritize the data analysis and daily happenings in the city, especially those narrated by the local press Jornal Correio as a way to perceive how the city of Uberlândia and its workers, as a consequence, are considered by the dominant class.